Design a CPW antenna on rubber substrate for multi-band applications - Sakib, Nazmus; Ibrahim, Siti Noorjannah; Ibrahimy, Muhammad Ibn; Mohamad, Sarah Yasmin; Mahfuz, M. M. Hasan (2020)
This paper presents a compact CPW monopole antenna on rubber sub-strate for multiband applications. The multi band applications (2.45 and 3.65 GHz) is achieved on this antenna design with better antenna performances. Spe-cially this antenna focused on ISM band application meanwhile some of slots (S1, S2, S3) have been used and attained another frequency band at 3.65 GHz for Wi-MAX application. The achievement of the antenna outcomes from this design that the bandwidth of 520 MHz for first band, the second band was 76 MHz for Wi-MAX application and the radiation efficiency attained around 90%. Moreo-ver, the realized gain was 4.27 dBi at 2.45 GHz which overcome the most of existing design on that field. The computer simulation technology (CST) micro-wave studio has been used for antenna simulation.